FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, and preparation method and application thereof

By constructing a FeOOH/Bi4TaO8Cl heterojunction and utilizing the interfacial micro-electric field to promote electron transfer, the problem of low Fe(IV)=O generation efficiency was solved, achieving efficient pesticide pollutant degradation and catalyst stability.

CN120695853BActive Publication Date: 2025-11-07JIANGXI AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511199253.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2025-11-07
Estimated Expiration
2045-08-26

AI Technical Summary

Technical Problem

In existing photo-Fenton technology, the Fe(IV)=O generation efficiency is low. The slow charge transfer process of the catalyst makes it difficult to break the OO bond, which affects the Fe(IV)=O generation efficiency. In addition, the Fe2+ regeneration capacity is limited, which affects the sustainability of the photo-Fenton reaction.

Method used

A heterojunction was constructed by combining amorphous FeOOH quantum dots with bismuth-based semiconductor Bi4TaO8Cl. Electron transfer was promoted by the point-to-surface micro-electric field at the interface, which increased the electron density of Fe-OH sites and enhanced the formation of Fe(IV)=O.

Benefits of technology

It improves catalytic activity, enhances the formation efficiency of Fe(IV)=O, achieves efficient activation of PMS, and achieves a pesticide pollutant degradation efficiency of up to 99.8%, while also exhibiting excellent anti-interference ability and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120695853B_ABST
    Figure CN120695853B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of photocatalyst, more particularly to a FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, a preparation method and application thereof.The amorphous FeOOH quantum dots are combined with bismuth-based semiconductor Bi4TaO8Cl to construct a heterojunction, so as to improve the catalytic reaction activity.In the present application, a point-surface microelectric field can be formed at the interface of FeOOH and Bi4TaO8Cl, which promotes the surface Fe-OH site and Fe-(O) OSO3 ‑ The electron transfer process between the complexes, the improvement of the electron density of the Fe-OH site provides a strong driving force, which is beneficial to the large production of Fe(IV)=O species in the catalytic system, so as to enhance the generation efficiency of Fe(IV)=O.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of photocatalysts, and more particularly to a FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, a preparation method and application thereof. BACKGROUND

[0002] The photo-Fenton technology of photocatalytic coupling based on PMS advanced oxidation process is considered as an effective technology for rapid treatment of pesticide pollution due to its green, efficient and sustainable. In this technology, the electron-hole pairs generated by photoexcitation of semiconductor can accelerate the activation of PMS to produce more active substances such as sulfate radical (SO4 •- ) and hydroxyl radical (·OH) to eliminate pesticide pollutants in water. However, the free radical degradation system mainly based on SO4 •- and ·OH is easily consumed by coexisting substrates, which is not conducive to the degradation of pesticides in actual water environment.

[0003] In recent years, a new non-radical oxidation mechanism has been proposed, i.e. M (IV)=O (M = Fe, Co) high-valent metal oxygen species. Fe (IV)=O and other high-valent metals have a long half-life (7s~10s) and strong anti-interference ability, which can directly oxidize target pollutants through hydrogen atom abstraction, oxygen atom transfer, electrophilic addition, etc. Compared with free radicals, Fe (IV)=O has a higher lifetime and anti-interference ability in water, and can maintain a high degradation efficiency in complex matrix water samples. The formation mechanism of Fe (IV)=O involves a complex-electron transfer process. First, a specific complex is formed between the catalyst and PMS through O-O bond, then the heterolysis of O-O bond in the complex is accompanied by a double electron transfer process to form Fe (IV)=O. In recent studies, iron-based oxides (Bi2Fe4O9, α-Fe2O3 and FeO) and iron-based hydroxides (ZnFe-LDH, CuFeAl-LDH, NiFe-LDH) and other catalysts have been widely reported to promote the formation of Fe (IV)=O. In contrast, iron-based hydroxide catalysts with abundant Fe-OH sites can effectively form Fe-(O) OSO3 - complex without additional hydration steps, and generate Fe (IV)=O species through an electron transfer process. However, due to the slow charge transfer process of this type of catalyst, it is difficult to break the O-O bond in the Fe-(O) OSO3 - complex, which affects the efficiency of Fe (IV)=O production. In addition, due to the limited regeneration ability of Fe 2+ , the accumulated Fe 3+ is difficult to participate in the next step of Fe (IV)=O generation, which affects the sustainability of the photo-Fenton reaction. SUMMARY

[0004] In order to solve the above problems, the application provides a FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst and a preparation method and application thereof. The amorphous FeOOH quantum dots are combined with the bismuth-based semiconductor Bi4TaO8Cl to construct a heterojunction, so as to improve the catalytic reaction activity. In the application, a point-plane microelectric field can be formed at the interface of FeOOH and Bi4TaO8Cl, so as to promote the surface Fe-OH site and Fe-(O) OSO3 - The electron transfer process between the complexes provides a strong driving force for improving the electron density of the Fe-OH site, which is beneficial to the large production of Fe(IV)=O species in the catalytic system, so as to enhance the generation efficiency of Fe(IV)=O.

[0005] The first object of the application is to provide a preparation method of the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst. In order to achieve the above object, the application provides the following technical scheme:

[0006] The preparation method of the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst comprises the following steps:

[0007] Step 1: Bi2O3, Ta2O5 and BiOCl are used as precursors, and Bi4TaO8Cl is prepared by a molten salt method;

[0008] The specific mode is as follows: Bi2O3, Ta2O5, BiOCl, NaCl and KCl are ground to obtain a uniform powder; the obtained powder is placed in a muffle furnace for calcination, and after natural cooling, the powder is washed with deionized water and ethanol for multiple times, and is dried at 80°C to obtain a yellow sample Bi4TaO8Cl;

[0009] Step 2: FeOOH quantum dots are modified to the surface of Bi4TaO8Cl by an in-situ deposition method to form a FeOOH / Bi4TaO8Cl composite material.

[0010] Further, the specific mode of the in-situ deposition method in step 2 is as follows: Bi4TaO8Cl is dispersed in a FeCl3·H2O anhydrous ethanol solution, and after ultrasonic treatment, it is stirred uniformly; then NH4HCO3 is added, and after stirring at room temperature for 8h~12h, the target product is collected; then the product is washed with deionized water and anhydrous ethanol, and the obtained product is dried in an oven at 80°C.

[0011] Further, the molar ratio of Bi2O3, Ta2O5, BiOCl, NaCl and KCl in step 1 is 1.5:0.5:1:10:10.

[0012] Further, the muffle furnace calcination temperature in step 1 is 750°C-780°C, and the reaction time is 3h-5h.

[0013] Further, the adding amount of Bi4TaO8Cl in step 2 is 0.025g-0.1g, and the preparation method of the FeCl3·H2O anhydrous ethanol solution is that 0.041g FeCl3·H2O is dissolved in 50mL-100mL anhydrous ethanol.

[0014] Further, the molar ratio of FeCl3·H2O to NH4HCO3 in step 2 is 1:3.

[0015] Further, the ultrasonic time in step 2 is 10min-30min, and the stirring time is 30min-60min.

[0016] The second object of the application is to provide a FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst prepared by the above preparation method.

[0017] Further, in the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, the mass percentage of FeOOH in the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst is 5%-20%.

[0018] Preferably, in the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, the mass percentage of FeOOH in the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst is 5%, 10% or 20%.

[0019] The third object of the application is to provide the application of the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst in catalytic degradation of pesticide pollutants in wastewater.

[0020] The technical scheme provided by the application has at least the following beneficial effects compared with the prior art:

[0021] 1、The application adopts a simple in-situ deposition method to combine amorphous FeOOH quantum dots and bismuth-based semiconductor Bi4TaO8Cl to construct a heterojunction, which is simple and does not generate impurity phases. - The interface between FeOOH and Bi4TaO8Cl can form a point-plane microelectric field, which provides a strong driving force for the electron transfer process between the complexes, improves the electron density of the Fe-OH site, and is beneficial to the generation of a large amount of Fe (IV)=O species in the catalytic system, thereby enhancing the generation efficiency of Fe (IV)=O and improving the catalytic reaction activity;

[0022] 2, The FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst prepared in the application can efficiently catalyze PMS to degrade pesticide pollutants in wastewater, and has excellent anti-interference ability. Under visible light irradiation, it efficiently catalyzes and activates PMS, and exhibits excellent photo-Fenton degradation performance on carbendazim, and the degradation efficiency is as high as 99.8%. BRIEF DESCRIPTION OF DRAWINGS

[0023] Figure 1 The XRD spectra of Bi4TaO8Cl, FeOOH quantum dots, FeOOH / Bi4TaO8Cl-10% catalyst prepared in Example 1, FeOOH / Bi4TaO8Cl-5% catalyst prepared in Example 2 and FeOOH / Bi4TaO8Cl-20% catalyst prepared in Example 3 are shown in Figure 1;

[0024] Figure 2 The morphology and element analysis diagrams of FeOOH / Bi4TaO8Cl-10% prepared in Example 1 are shown in Figure 2; wherein, Figure 2 a is the SEM diagram in the figure, Figure 2 b is the TEM diagram in the figure, Figure 2 c is the HRTEM diagram in the figure, Figure 2 d is the EDS diagram in the figure;

[0025] Figure 3 The degradation efficiency characterization diagrams of various catalysts on different pollutants are shown in Figure 3; wherein, Figure 3 a and Figure 3 b are respectively the dynamic curve and kinetic fitting of FeOOH quantum dots, Bi4TaO8Cl and FeOOH / Bi4TaO8Cl-10%, FeOOH / Bi4TaO8Cl-5% and FeOOH / Bi4TaO8Cl-20% on the photo-Fenton degradation of carbendazim solution; Figure 3 c is the degradation rate diagram of four systems of PMS, FeOOH / Bi4TaO8Cl-10% / PMS, FeOOH / Bi4TaO8Cl-10% / Vis and FeOOH / Bi4TaO8Cl-10% / PMS / Vis on carbendazim; Figure 3 d is the degradation effect diagram of FeOOH / Bi4TaO8Cl-10% catalyst in activating PMS to degrade carbendazim under visible light irradiation for multiple cycles; Figure 3 e is the degradation efficiency diagram of FeOOH / Bi4TaO8Cl-10% catalyst in catalyzing and activating PMS to degrade different pollutants under light irradiation; Figure 3 f is the degradation rate comparison diagram of FeOOH / Bi4TaO8Cl-10% catalyst, Fe 2+ , commercial Fe2O3 and Fe3O4 in catalyzing and activating PMS to degrade carbendazim under light irradiation;

[0026] Figure 4 Figure for the effect of common coexisting ions in solution on the degradation rate of carbendazim in the FeOOH / Bi4TaO8Cl-10% catalyst / PMS / Vis system;

[0027] Figure 5 Figure for the study of various data of the FeOOH / Bi4TaO8Cl-10% catalyst catalytic activation reaction mechanism; wherein, Figure 5 Figure for the effect of different free radical trapping agents on the degradation rate of carbendazim in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis system in Example a; Figure 5 Figure for the detection of Fe(IV) in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis system in Example b; Figure 5 Figure for the detection of Fe(IV) in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis system in Example c and Figure 5 Figure for the detection of Fe(IV) in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis system in Example d. DETAILED DESCRIPTION

[0028] In order for those skilled in the art to more clearly understand the present application, the present application will be further described in detail below in conjunction with the examples and drawings, but it should be understood that the following examples are only preferred embodiments of the present application, and the scope of the present application should be limited by the scope defined in the claims.

[0029] In the description of the present application, it should be noted that, in the examples, the specific conditions not specified are carried out according to the conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be purchased on the market.

[0030] In the description of the present application, BTOC in the drawings of the specification represents Bi4TaO8Cl.

[0031] Example 1

[0032] The present embodiment provides a preparation method of a FeOOH / Bi4TaO8Cl heterojunction Fenton catalyst, comprising the following steps:

[0033] Step 1, grind Bi2O3, Ta2O5, BiOCl, NaCl and KCl in a molar ratio of 1.5:0.5:1:10:10 to obtain a uniform powder; place the obtained powder in a muffle furnace for calcination, the calcination temperature is 750°C, and the reaction time is 3h; after natural cooling, wash the yellow sample Bi4TaO8Cl with deionized water and ethanol for multiple times, and dry at 80°C to obtain the yellow sample Bi4TaO8Cl;

[0034] Step 2, 0.041 g FeCl3-H2O was dissolved in 50 mL absolute ethanol, 0.05 g Bi4TaO8Cl was dispersed in the FeCl3-H2O absolute ethanol solution, and after ultrasonic treatment for 10 min, stirring was performed for 30 min;

[0035] Subsequently, NH4HCO3 was added, and the molar ratio of NH4HCO3 to FeCl3-H2O was 1:3; after stirring at room temperature for another 8 h, the target product was collected; then, the product was washed with deionized water and absolute ethanol, and the obtained product was dried in an oven at 80°C.

[0036] In the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst prepared in this example, the mass percentage of FeOOH in the composite material (i.e., FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst) was 10%, denoted as FeOOH / Bi4TaO8Cl-10%.

[0037] Example 2

[0038] The present example provides a preparation method of a FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, comprising the following steps:

[0039] Step 1, Bi2O3, Ta2O5, BiOCl, NaCl and KCl were ground in a molar ratio of 1.5:0.5:1:10:10 to obtain a uniform powder; the obtained powder was placed in a muffle furnace for calcination, the calcination temperature was 780°C, and the reaction time was 4 h. After natural cooling, the sample was washed with deionized water and ethanol for several times, and dried at 80°C to obtain a yellow sample Bi4TaO8Cl;

[0040] Step 2, 0.041 g FeCl3-H2O was dissolved in 50 mL absolute ethanol, 0.1 g Bi4TaO8Cl was dispersed in the FeCl3-H2O absolute ethanol solution, and after ultrasonic treatment for 20 min, stirring was performed for 40 min;

[0041] Subsequently, NH4HCO3 was added, and the molar ratio of NH4HCO3 to FeCl3-H2O was 1:3; after stirring at room temperature for another 8 h, the target product was collected; then, the product was washed with deionized water and absolute ethanol, and the obtained product was dried in an oven at 80°C.

[0042] In the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst prepared in this example, the mass percentage of FeOOH in the composite material was 5%, denoted as FeOOH / Bi4TaO8Cl-5%.

[0043] Example 3

[0044] The embodiment provides a preparation method of a FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, and comprises the following steps:

[0045] Step 1, Bi2O3, Ta2O5, BiOCl, NaCl and KCl are ground in a molar ratio of 1.5:0.5:1:10:10 to obtain a uniform powder; the obtained powder is placed in a muffle furnace for calcination, the calcination temperature is 760°C, and the reaction time is 5h. After natural cooling, the powder is washed with deionized water and ethanol for multiple times, and dried at 80°C to obtain a yellow sample Bi4TaO8Cl;

[0046] Step 2, 0.041g of FeCl3·H2O is dissolved in 100mL of anhydrous ethanol, and 0.025g of Bi4TaO8Cl is dispersed in the anhydrous ethanol solution of FeCl3·H2O, and then ultrasonic treatment is performed for 30min, followed by stirring for 60min;

[0047] Then, NH4HCO3 is added, and the molar ratio of FeCl3·H2O to NH4HCO3 is 1:3; the target product is collected after stirring at room temperature for 8h; then the product is washed with deionized water and anhydrous ethanol, and the obtained product is dried in an oven at 80°C.

[0048] In the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst prepared in the embodiment, the mass percentage of FeOOH in the composite material is 20%, and the catalyst is denoted as FeOOH / Bi4TaO8Cl-20%.

[0049] Material characterization

[0050] 1, the crystal structures of Bi4TaO8Cl (obtained in step 1 of the embodiment 1), FeOOH quantum dots (the method in step 2 of the embodiment 1 is adopted, but Bi4TaO8Cl is not added), the FeOOH / Bi4TaO8Cl-10% catalyst prepared in the embodiment 1, the FeOOH / Bi4TaO8Cl-5% catalyst prepared in the embodiment 2 and the FeOOH / Bi4TaO8Cl-20% catalyst prepared in the embodiment 3 are characterized by XRD, and the results are shown in Figure 1 , (Bi4TaO8Cl is denoted as BTOC in the drawing). As shown in Figure 1As shown in FIG. 6, the XRD pattern of FeOOH quantum dots does not exhibit obvious diffraction peaks, indicating that no crystallization occurs, and ideal amorphous FeOOH quantum dots are obtained. For Bi4TaO8Cl, the sample diffraction peaks correspond well to the orthorhombic phase of Bi4TaO8Cl (JCPMS No. 54-0124). For FeOOH / Bi4TaO8Cl, the FeOOH quantum dots in-situ anchored on the surface of Bi4TaO8Cl do not change the overall crystallinity, indicating that Bi4TaO8Cl has high stability in the quantum dot formation process. In addition, no additional peaks appear in the XRD pattern of the FeOOH / Bi4TaO8Cl composite material, indicating that the FeOOH / Bi4TaO8Cl heterojunction Fenton-like catalyst composite material is successfully prepared and no impurity phase is generated.

[0051] 2. The FeOOH / Bi4TaO8Cl-10% catalyst prepared in Example 1 was tested by scanning electron microscopy (SEM) combined with energy dispersive X-ray spectroscopy (EDS) spectrometer, and the SEM image is shown in FIG. 7a, and the EDS image is shown in FIG. 7d. Figure 2 Figure 2 Figure 2 As shown in FIG. 7a, the prepared FeOOH / Bi4TaO8Cl-10% presents a nanosheet morphology with an average width of about 0.3 μm~1 μm and a thickness of about 200 nm, and the amorphous FeOOH quantum dot particle size distribution is highly uniform, and the nanosheet surface has no obvious FeOOH quantum dot agglomeration. Figure 2 The EDS image analysis in FIG. 7d shows that the Cl, Bi, O, Ta and Fe elements are uniformly distributed in the FeOOH / Bi4TaO8Cl-10% catalyst composite material.

[0052] The morphology and structure of FeOOH / Bi4TaO8Cl-10% were further characterized by TEM and HRTEM, and the results are shown in FIG. 7b and FIG. 7c. As shown in FIG. 7b, the amorphous FeOOH quantum dots with a size of 4 nm~8 nm are uniformly distributed on the surface of Bi4TaO8Cl and closely contact with each other, which is conducive to the electron transfer at the interface between Bi4TaO8Cl and amorphous FeOOH quantum dots, and the morphology and diameter of FeOOH / Bi4TaO8Cl are consistent with the SEM results. As shown in FIG. 7c, the lattice spacing of 0.430 nm points to the (104) face of Bi4TaO8Cl. The above results show that the FeOOH / Bi4TaO8Cl catalyst forms a tight heterojunction interface. Figure 2 Figure 2 Figure 2 Figure 2

[0053] In addition, the UV-Vis absorption spectrum of the FeOOH / Bi4TaO8Cl-10% catalyst is shown in FIG. 8. As shown in FIG. 8, the absorption edge of the FeOOH / Bi4TaO8Cl-10% catalyst is red-shifted compared with that of Bi4TaO8Cl, indicating that the FeOOH / Bi4TaO8Cl-10% catalyst has a wider absorption range and higher visible light utilization efficiency. Figure 2 ​​​​​​EDS mapping of the middle d shows that the Cl, Bi, O, Ta and Fe elements are uniformly distributed in the FeOOH / Bi4TaO8Cl-10% composite.

[0054] Performance characterization

[0055] 1. Test catalytic activation performance

[0056] Selecting carbendazim as a representative of pollutants, Bi4TaO8Cl (obtained in step 1 of Example 1), FeOOH quantum dots (using the method of step 2 of Example 1, but without adding Bi4TaO8Cl), FeOOH / Bi4TaO8Cl-10% catalyst prepared in Example 1, FeOOH / Bi4TaO8Cl-5% catalyst prepared in Example 2 and FeOOH / Bi4TaO8Cl-20% catalyst prepared in Example 3 were used to activate PMS to degrade carbendazim. Experimental method: 500 mL of 10 mg / L carbendazim solution was prepared, and 50 mL of the carbendazim solution was taken in a beaker; 12 mg of FeOOH quantum dots, Bi4TaO8Cl and FeOOH / Bi4TaO8Cl-10% catalyst, FeOOH / Bi4TaO8Cl-5% catalyst and FeOOH / Bi4TaO8Cl-20% catalyst powders were weighed and added to the carbendazim pollutant solution, respectively, and stirred uniformly to reach adsorption-desorption equilibrium; then, 16 mg of PMS was weighed and added to the pollutant solution containing different catalysts, and under the irradiation of a 300 W xenon lamp (containing a 420 nm filter), 1 mL of the reaction solution was taken every 5 min for testing the content of carbendazim. The test results are shown in Figure 3 , (BTOC in the figure represents Bi4TaO8Cl).

[0057] Figure 3 Middle a and Figure 3 Middle b are the dynamic curves and kinetic fitting of FeOOH quantum dots, Bi4TaO8Cl and FeOOH / Bi4TaO8Cl-10%, FeOOH / Bi4TaO8Cl-5% and FeOOH / Bi4TaO8Cl-20% for photofenton degradation of carbendazim solution, respectively. From Figure 3 Middle a and Figure 3 Middle b can be known that under the synergistic action of visible light and PMS, the FeOOH / Bi4TaO8Cl catalysts can effectively activate PMS to degrade carbendazim, especially, the FeOOH / Bi4TaO8Cl-10% sample with 10% FeOOH mass fraction reached a 99.8% degradation rate of carbendazim within 30 min, and its degradation rate constant was 6.46 times and 164 times that of FeOOH quantum dots and Bi4TaO8Cl, respectively.

[0058] The same test method was used to test four groups of samples, namely PMS only, FeOOH / Bi4TaO8Cl-10% combined with PMS (FeOOH / Bi4TaO8Cl-10% / PMS), FeOOH / Bi4TaO8Cl-10% under light (i.e. FeOOH / Bi4TaO8Cl-10% / Vis), and FeOOH / Bi4TaO8Cl-10% and PMS under light (i.e. FeOOH / Bi4TaO8Cl-10% / PMS / Vis). The test results are shown in Table C. Figure 3

[0059] Figure 3 Table C is a graph showing the degradation rate of carbendazim in the four systems of PMS, FeOOH / Bi4TaO8Cl-10% / PMS, FeOOH / Bi4TaO8Cl-10% / Vis, and FeOOH / Bi4TaO8Cl-10% / PMS / Vis. As can be seen from Table C, Figure 3

[0060] 2. Test the cycle stability

[0061] The FeOOH / Bi4TaO8Cl-10% catalyst prepared in Test Example 1 was tested for its performance in activating PMS to degrade carbendazim under visible light irradiation for multiple cycles, and the Fe ion leaching in the photo-Fenton system.

[0062] Test method: 500 mL of a 10 mg / L carbendazim solution was prepared, 50 mL of the carbendazim solution was taken in a beaker, 12 mg of the FeOOH / Bi4TaO8Cl-10% catalyst prepared in Example 1 was added to the carbendazim solution, and the mixture was stirred until adsorption-desorption equilibrium was reached. Then 16 mg of PMS was added to the catalyst-containing carbendazim solution, and under the irradiation of a 300 W xenon lamp (with a 420 nm filter), 1 mL of the reaction solution was taken every 30 min for testing the content of carbendazim. The catalyst after recovery was tested, and the above steps were repeated to test its cycle stability. Figure 3 ​​Figure 1 shows the degradation efficiency of the FeOOH / Bi4TaO8Cl-10% catalyst in the PMS activation under visible light irradiation for multiple cycles to degrade carbofuran.

[0063] Figure 1 shows the degradation efficiency of the FeOOH / Bi4TaO8Cl-10% catalyst in the PMS activation under visible light irradiation for multiple cycles to degrade carbofuran. Figure 3 As shown in Figure 1, the FeOOH / Bi4TaO8Cl-10% catalyst has a degradation efficiency of carbofuran of 90% after 5 cycles of PMS activation under visible light irradiation, which maintains a high degradation efficiency of carbofuran. In addition, the concentration of Fe metal ions in the system is calculated by flame atomic absorption spectrophotometry, and the leaching concentration of Fe metal ions is less than 180 µg / L after 5 cycles of experiments, which is significantly lower than the limited value (1 mg / L) of the Environmental Quality Standard for Surface Water (GB3838-2002) of China, indicating that the catalyst has excellent cycle stability.

[0064] 3. Research applicability and practicality

[0065] Research method: 500 mL of 10 mg / L carbofuran, tetracycline, rhodamine B, bisphenol A and atrazine solutions were prepared respectively, and 50 mL of sample solution was taken in a beaker; 12 mg of FeOOH / Bi4TaO8Cl-10% catalyst, commercial Fe2O3, Fe 2+ ions and Fe3O4 catalysts were added to different pollutant solutions respectively, and stirred uniformly to reach adsorption-desorption equilibrium; then 16 mg of PMS was added to the pollutant solution with different catalysts, and under the irradiation of a 300 W xenon lamp (with a 420 nm filter), 1 mL of reaction solution was taken every 5 min for testing the content of pollutants.

[0066] Figure 3 Figure 1 shows the degradation efficiency of the FeOOH / Bi4TaO8Cl-10% catalyst in the PMS activation under visible light irradiation for multiple cycles to degrade carbofuran. Figure 3 As shown in Figure 1, the FeOOH / Bi4TaO8Cl-10% catalyst has a degradation efficiency of carbofuran of 90% after 5 cycles of PMS activation under visible light irradiation, which maintains a high degradation efficiency of carbofuran. In addition, the concentration of Fe metal ions in the system is calculated by flame atomic absorption spectrophotometry, and the leaching concentration of Fe metal ions is less than 180 µg / L after 5 cycles of experiments, which is significantly lower than the limited value (1 mg / L) of the Environmental Quality Standard for Surface Water (GB3838-2002) of China, indicating that the catalyst has excellent cycle stability. Figure 3 Figure 1 shows the degradation efficiency of the FeOOH / Bi4TaO8Cl-10% catalyst in the PMS activation under visible light irradiation for multiple cycles to degrade carbofuran. 2+ Figure 1 shows the degradation efficiency of the FeOOH / Bi4TaO8Cl-10% catalyst in the PMS activation under visible light irradiation for multiple cycles to degrade carbofuran. Figure 4 As shown in Figure 1, the FeOOH / Bi4TaO8Cl-10% catalyst has a degradation efficiency of carbofuran of 90% after 5 cycles of PMS activation under visible light irradiation, which maintains a high degradation efficiency of carbofuran. In addition, the concentration of Fe metal ions in the system is calculated by flame atomic absorption spectrophotometry, and the leaching concentration of Fe metal ions is less than 180 µg / L after 5 cycles of experiments, which is significantly lower than the limited value (1 mg / L) of the Environmental Quality Standard for Surface Water (GB3838-2002) of China, indicating that the catalyst has excellent cycle stability. Figure 4 As shown in Figure 1, the FeOOH / Bi4TaO8Cl-10% catalyst has a degradation efficiency of carbofuran of 90% after 5 cycles of PMS activation under visible light irradiation, which maintains a high degradation efficiency of carbofuran. In addition, the concentration of Fe metal ions in the system is calculated by flame atomic absorption spectrophotometry, and the leaching concentration of Fe metal ions is less than 180 µg / L after 5 cycles of experiments, which is significantly lower than the limited value (1 mg / L) of the Environmental Quality Standard for Surface Water (GB3838-2002) of China, indicating that the catalyst has excellent cycle stability.

[0067] 4. Test anti-interference capability

[0068] Test method: Prepare 500 mL of 10 mg / L carbendazim solution, and measure 50 mL of the carbendazim solution into a beaker; weigh 12 mg of FeOOH / Bi4TaO8Cl-10% catalyst and 0.1 mol / L inorganic salt and add them separately to the carbendazim solution (no inorganic salt added, only catalyst is the blank group), stir well to reach adsorption-desorption equilibrium; then weigh 16 mg of PMS and add it to the carbendazim solution with added catalyst and different inorganic salts. Under irradiation with a 300W xenon lamp source (with a 420 nm filter), take 1 mL of the reaction solution every 5 minutes to test the carbendazim content. Test results are as follows. Figure 4 As shown.

[0069] Figure 5 This figure shows the effect of common coexisting ions in solution on the degradation rate of carbendazim in the FeOOH / Bi4TaO8Cl-10% catalyst / PMS / Vis system. Figure 5 It can be seen that most ions have little effect on the degradation rate of carbendazim by FeOOH / Bi4TaO8Cl-10% catalyst / PMS / Vis. The FeOOH / Bi4TaO8Cl / PMS / Vis system has good anti-interference ability.

[0070] 5. Study the reaction mechanism

[0071] Research Methods: Prepare 500 mL of 10 mg / L carbendazim solution, and measure 50 mL of the carbendazim solution into a beaker; weigh 12 mg of FeOOH quantum dots, Bi4TaO8Cl and FeOOH / Bi4TaO8Cl-10% catalyst and 0.1 mol / L of different free radical scavengers respectively and add them to the carbendazim solution, stirring until adsorption-desorption equilibrium is reached; then, weigh 16 mg of PMS and add it to the carbendazim solution, and under irradiation with a 300 W xenon lamp source (including a 420 nm filter), take 1 mL of the reaction solution every 5 min to test the carbendazim content.

[0072] Figure 5 Figure 'a' shows the effect of different free radical scavengers on the degradation rate of carbendazim in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis system. Figure 5 As shown in section a, BQ and EDTA have no significant effect on the degradation of carbendazim. When methanol and TBA are added, the degradation rate of carbendazim decreases from 99.8% to 72.3% and 81.4%, respectively, indicating that •OH and SO42- have little effect on its degradation. •- To some extent, they all participated in the degradation of carbendazim. In addition, DMSO can react with Fe(IV) (1.26 × 10⁻⁶). 5 M −1 ·s−1 •OH (7.0 ×10) 9 M −1 ·s −1 ) and SO4 •- (2.7 × 10) 9 M −1 ·s −1 Rapid reaction. Compared with MeOH, DMSO showed a strong inhibitory effect, indicating that Fe(IV) may play a major role in the degradation of carbendazim.

[0073] To further confirm the presence of Fe(IV), PMSO was used as a probe because it is converted to PMSO2 by Fe(IV), but to SO42-. •- •OH was converted to biphenyl and hydroxyl products, respectively. Methods: 500 mL of a 10 mg / L carbendazim solution was prepared. 50 mL of the carbendazim solution was placed in a beaker. 12 mg of FeOOH quantum dots, Bi₄TaO₈Cl, and FeOOH / Bi₄TaO₈Cl-10% catalyst were weighed and mixed with a 1 mmol / L PMSO aqueous solution. The mixture was stirred until adsorption-desorption equilibrium was reached. Then, 16 mg of PMS was added to the carbendazim solution. Under irradiation with a 300 W xenon lamp (with a 420 nm filter), 1 mL of the reaction solution was taken every 5 minutes to test the PMSO and PMSO₂ content. Results are as follows: Figure 5 As shown in b.

[0074] Figure 5 Figure b shows the data for Fe(IV) detection by PMSO in the FeOOH / Bi₄TaO₈Cl-10% / PMS / Vis system. Figure 5 As shown in b, the gradual loss of PMSO and the formation of PMSO2 were quantified, with 0.073 mmol / L PMSO being oxidized, producing 0.060 mmol / L PMSO2 after 30 min. -1 The yield of PMSO2 (η(PMSO2)) was as high as 77.3%, which proves the transformation of PMSO to PMSO2. This result indicates that FeOOH / Bi4TaO8Cl-10% can effectively generate Fe(IV).

[0075] Using 5,5-dimethyl-1-pyrrole-N-oxide (DMPO) and 2,2,6,6-tetramethyl-4-piperidinol (TEMP) as spin trapping reagents, the ROS generated in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis system was measured by EPR. The test results are as follows: Figure 5 c and Figure 5 As shown in Figure d (BTOC is represented as Bi4TaO8Cl in the attached figure). From Figure 5As can be seen from c, TEMP- was detected in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis process. 1 The O2 adduct disappears in the presence of p-BQ. ​ (d). This indicates that... 1 The generation of O2 may be related to •O2 - The transformation is involved, rather than a direct interaction between FeOOH / Bi4TaO8Cl-10% and the PMS activation process. Furthermore, a set of signals with seven peaks was observed in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis process; these signals belong to 5,5-dimethyl-2-oxo-pyron-1-oxo (DMPOX), not DMPO-SO4. •- Or DMPO-•OH and adducts. Studies have confirmed that DMPO can be reacted with non-free radicals (Fe(IV) or... 1 O2) is oxidized to DMPOX. (In the exclusion...) 1 After O2 contributes to the generation of DPMOX, the DMPOX signal does not change significantly. Therefore, high-valence iron oxide is only related to the generation of DMPOX. These results strongly demonstrate the presence of high-valence iron and its important role in the FeOOH / Bi4TaO8Cl-10% / PMS / Vis system.

[0076] The above description is merely a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the concept described herein through the above teachings or related technologies or knowledge. Modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. A preparation method of FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, characterized in that, Comprising the following steps: Step 1, using Bi2O3, Ta2O5 and BiOCl as precursors, Bi4TaO8Cl is prepared by a molten salt method; The specific method is as follows: Bi2O3, Ta2O5, BiOCl, NaCl and KCl are ground to obtain a uniform powder; the obtained powder is placed in a muffle furnace for calcination, and after natural cooling, it is washed with deionized water and ethanol for several times, and dried at 80°C to obtain a yellow sample Bi4TaO8Cl; The muffle furnace calcination temperature is 750°C~780°C, and the reaction time is 3h~5h; Step 2, FeOOH quantum dots are modified to the surface of Bi4TaO8Cl by an in-situ deposition method to form a FeOOH / Bi4TaO8Cl composite material; The specific method of the in-situ deposition method is as follows: Bi4TaO8Cl is dispersed in a FeCl3·H2O anhydrous ethanol solution, and after ultrasonic stirring, it is uniformly stirred; then NH4HCO3 is added, and after stirring at room temperature for 8h~12h, the target product is collected; then it is washed with deionized water and anhydrous ethanol, and the obtained product is dried in an oven at 80°C; The mass percentage of FeOOH in the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst is 5%~20%.

2. The preparation method of the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst according to claim 1, characterized in that, The molar ratio of Bi2O3, Ta2O5, BiOCl, NaCl and KCl in step 1 is 1.5:0.5:1:10:

10.

3. The preparation method of the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst according to claim 1, characterized in that, In step 2, the addition amount of Bi4TaO8Cl is 0.025g~0.1g, and the preparation method of the FeCl3·H2O anhydrous ethanol solution is to dissolve 0.041g FeCl3·H2O in 50mL~100mL anhydrous ethanol.

4. The preparation method of the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst according to claim 1, characterized in that, In step 2, the molar ratio of FeCl3·H2O to NH4HCO3 is 1:

3. 5.The method for preparing FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst according to claim 1, characterized in that, In step 2, the ultrasonic time is 10min~30min, and the stirring time is 30min~60min.

6. A FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, characterized in that, The FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst is prepared by the preparation method of any one of claims 1~5.

7. The application of the FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst of claim 6 in catalytic degradation of pesticide pollutants in wastewater.

Citation Information

Patent Citations

  • Easy-to-recycle magnetic visible-light-induced photocatalyst and preparation method thereof

    CN111715277A

  • Preparation method of Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst as well as product and application of Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst

    CN119236986A